Pengaruh Komisaris Independen dan Indeks Islamic Social Reporting Terhadap Nilai Perusahaan dengan Profitabilitas Sebagai Variabel Intervening - Robbi Hasana Ibrahim; Ahmad Mifdlol Muthohar (ITB AAS INDONESIA Surakarta, 2019)
The purpose of this study was to determine the effect of independent board of commissioners and Islamic Social Reporting index on firm value with profitability (ROE) as an intervening variable. This research is quantitative in nature which uses secondary data with a purposive sampling method, obtained by 30 companies listing in the Indonesian Syariah Stock Index in 2015-2017. This study uses multiple linear regression analysis and path analysis to test the effect of intervening variables. The results of data processing show that the independent board of commissioners, Islamic Social Reporting index and profitability simultaneously have a significant positive effect on firm value (Tobin-Q). While partially shows that the independent board of commissioners does not affect the value of the company either directly or indirectly. The disclosure of the Islamic Social Reporting Index has a significantly positive effect on firm value indirectly through profitability. Profitability (ROE) significantly influences the value of the company listing in the Indonesian Islamic Stock Index.